On sex, drugs, and alcohol: a mixed-method analysis of youth posts on social media in the United States. Issue 4 (2nd October 2022) - Stevens, Robin; Bonett, Stephen; Kenyatta, Kahaari; Chittamuru, Deepti; Bleakley, Amy; Jingyi Xu, Jackie; Wang, Yunwen; Bush, Nicole
ABSTRACT: In the digital neighborhood, Black and Hispanic youth communicate about issues they face, including sex and substance use. This population of young people is also disproportionately burdened by negative consequences associated with sex and substance use behaviors even when their behavior is less risky. Given the increased likelihood of negative outcomes, we investigated how young people communicate about these behaviors in their digital social networks. This mixed-methods study integrates a behavioral survey with a machine learning-supported, qualitative content analysis of one year of Facebook and Twitter posts from 50 Black and Hispanic youth, with feedback from a youth advisory board. Participants who had previously had sex or drank alcohol were more likely to post about sex or alcohol, respectively. Moreover, compared to male youth, female youth posted significantly more about sex in general and about STIs, HIV, and pregnancy . Posts about sexual behavior often discussed trust in sexual partners and gendered views of sex. Posts linked alcohol and marijuana with stress relief and coping withgrief, community violence, and distress. Understanding how youth think and communicate about sexual risk and substance use can inform the design of effective prevention efforts. IMPACT SUMMARY: Prior State of Knowledge : Social media offers an excellent window into youth perspectives and the ways they broadcast and communicate about their lives, beliefs, and health behaviors to their networked peers. Novel Contributions : In this community-engaged study, we center the experiences of Black and Hispanic youth in their digital neighborhoods to understand how youth talk about sex, drugs and alcohol in their own words . We examined the interplay between posts, social identities and health behaviors. Practical Implications : For practitioners using social media in prevention efforts, integrating youth voices and expertise in the development of online prevention efforts may be more effective in identifying drivers of risk taking and supporting risk reduction behavior.